Evaluation of triglyceride-glucose index, triglyceride to high-density lipoprotein cholesterol ratio, and other lipid ratios in hypertension - Kiro, Jyotsna; Acharya, Madhusmita; Bhoi, Sumitra; Bhoi, Sanghamitra; Tirkey, Neelam B (Asian Journal of Medical Sciences, 2023)
Background: Hypertension is one of the most common diseases with increasing morbidity and mortality. HTN is associated with cardiovascular risk factors such as insulin resistance (IR) and hyperlipidemia. Recently, triglyceride-glucose (TyG) index has been proposed as a marker for insulin resistance. Aims and Objectives: This study aimed to assess TyG index, triglyceride to high-density lipoprotein ratio, and other lipid ratios in HTN patients. Materials and Methods: The present study was conducted on 200 subjects and was categorized into two groups. 100 hypertensive patients were considered as cases and 100 healthy individuals as controls. Serum sample of the subjects was used for the estimation of total cholesterol, triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C). Low-density lipoprotein (LDL) cholesterol was calculated. TyG index and TG/HDL ratio and other lipid ratios were calculated. Blood pressure (BP) was recorded. Results: In this, BP, total cholesterol, TG, LDL, Very low-density lipoprotein cholesterol, Non-HDLC, TC/HDL ratio, TG/HDL ratio, and TyG index were increased in cases and HDL and HDL/LDL ratio were decreased. Study parameters were positively correlated with TyG index and TG/HDL ratio, except HDL, and HDL/LDL ratio. Conclusion: The study concludes that significantly increased TyG index and TG/HDL ratio in hypertensive cases and their correlation with blood pressure.